2020
DOI: 10.33545/surgery.2020.v4.i2g.453
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison on surgical management of varicose veins with and without venous stripping

Abstract: Varicose veins, one of the oldest known diseases of mankind were treated by various modalities starting from simple phlebotomy to minimally invasive approaches. Aim and Objectives: In this study the outcome of two surgical treatment modalities of varicose surgery with and without venous stripping was compared based upon a follow up period of two months. Materials and Methods: Among the 92 patients operated for varicose veins between September 2018 to November 2019 in all surgical units of Trichy SRM Medical Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In the study of Natraj et al the hematoma formation after venous stripping was 28% whereas it was only 4% in the other group. 10 In the present study, on the first post-operative day, 73.33% of those who underwent stripping and 80% from those who underwent ligation alone had comfortable ambulation. In the study of Natraj et al there was no significant difference in healing of leg wounds in both the studies.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…In the study of Natraj et al the hematoma formation after venous stripping was 28% whereas it was only 4% in the other group. 10 In the present study, on the first post-operative day, 73.33% of those who underwent stripping and 80% from those who underwent ligation alone had comfortable ambulation. In the study of Natraj et al there was no significant difference in healing of leg wounds in both the studies.…”
Section: Discussionmentioning
confidence: 42%
“…In the study of Natraj et al long postoperative stay of more than 6 days was found in 8% of those who underwent stripping and 4% of the other group where as in present study, 13.3% patients of venous stripping group and 6.66% patients of trendelenberg surgery alone group had prolonged hospital stay. 10 In this study, pain relief was seen in 93.33% of those who had venous stripping and 96.66% of those who did not undergo venous stripping at the end of second month. All these findings are comparable with the studies of…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation